Criminal Sanctions against Threats of Violence Through Social Media - Luh Putu Suryani; I Nyoman Gede Sugiartha; Ni Made Puspasutari Ujianti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
It is undeniable that technological advances are increasingly affecting human life to facilitate human activities. With the many facilities offered, it is easier for humans to do things that are not in accordance with what they should do, such as committing crimes of threats of violence through social media that are rife in today's society. With this, the Indonesian government has issued several rules for law enforcement against perpetrators of criminal acts of threats of violence through social media as regulated in Article 335 paragraph (1) 369 paragraph (1) of the Criminal Code and Article 45B of the ITE Law. In this study, the causes of perpetrators of criminal acts of threatening violence through social media are explored and examined more deeply, besides that, criminal sanctions are also carefully examined for perpetrators of criminal acts of threats of violence through social media. This research uses normative legal research type. The cause of the perpetrators of these crimes needs to be known so that the public remains vigilant. Then regarding the sanctions that will be imposed on the perpetrators in accordance with the Criminal Code and the ITE Law.